(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2024)
Energy conservation is a critical priority for educational institutions, aiming to reduce operational costs and minimize environmental impact. This paper explores the role of information technology (IT) in managing energy efficiency within academic facilities. Key IT solutions, such as energy monitoring systems, automated controls, and data analytics, are highlighted as essential tools to optimize energy use. The benefits of adopting these technologies include cost savings, improved operational efficiency, and enhanced sustainability. Despite challenges such as high initial investment and technical expertise requirements, the integration of IT presents a promising pathway for sustainable energy management. The paper concludes with practical recommendations for educational institutions to effectively implement IT-driven energy conservation strategies.